Gender Inequality and Women Participation in Political Activities and Peace Processes in Rivers State, Nigeria - Badom Porbari Monbari; Ndeeue Kuapie (European Review Of Applied Sociology)
Gender inequality is endemic in Rivers State, and women are treated as Cinderella in peace processes, decision making and active political participation, and have thus been shackled in diverse ways, but behind the pretext of being otherwise engaged with culturally attributed motherly roles. Gender discrimination had thus lingered with solipsistic men who occupy positions of authority in the majority, and inured the women to the condition, apropos of gender inequality, as the elephant in the living room. This was however unsubstantiated, hence the study is a cutting edge of intellectual response which studied gender inequality and women participation in political activities and peace processes in Rivers State. The study is a cross sectional survey which triangulated data collection. Sample size was 400, determined by Taro Yamane statistics from the population size. Random and simple random sampling methods were adopted in the selection of the communities and respondents. The quantitative data were analyzed with ordinal level statistics and chi-square adopted in testing the hypotheses. The qualitative data were content analyzed. The study found that gender inequality hinders women from becoming members of conflict resolution committees, hinders the appointment of women at community decision making levels, and also hinders women from participating in active politics in Rivers State. Thereafter, policy recommendations were made.